Answer:
![-p^2+32](https://tex.z-dn.net/?f=-p%5E2%2B32)
Step-by-step explanation:
Start by expanding the
into the
bracket using the distributive method:
![-2(p-4)\\-2p + 8](https://tex.z-dn.net/?f=-2%28p-4%29%5C%5C-2p%20%2B%208)
Now, expand the result into the remaining bracket:
![(-2p + 8)(p+4)\\-2p^2 -8p+8p+32\\-2p^2 + 32](https://tex.z-dn.net/?f=%28-2p%20%2B%208%29%28p%2B4%29%5C%5C-2p%5E2%20-8p%2B8p%2B32%5C%5C-2p%5E2%20%2B%2032)
Answer:
Answer:
3x + 3y = 0
7x - y = 8
Step-by-step explanation:
Answer:
194.
Step-by-step explanation:
x = (7+4√3)
x^2 = x = (7+4√3)^2
= 49 + 48 + 56√3
= 97 + 56√3
x^2 + 1/x^2 = 97 + 56√3 + 1/(97 + 56√3)
= 194.
Answer:
A≈1075.21
d Diameter
37
d
r
r
r
d
d
C
A
Using the formulas
A=
π
r
2
d=
2
r
Solving forA
A=
1
4
π
d
2
=
1
4
π
37
2
≈
1075.21009
Step-by-step explanation:
Answer:
y = -3x - 3
Step-by-step explanation:
First, determine the slope of the red line. As we move from (0, 3) to (1, 0),
x increases by 1 and y decreases by 3. Hence, the slope, m, is
m = rise / run = -3 / 1, or m = -3.
The desired new line, parallel to the red line, has the same slope as the red line: m = -3.
The equation for this new line is y - k = m (x - h), where (h, k): (-1, 0):
We get y - 0 = -3 (x + 1), or y = -3x - 3.
Check: Does this line go thru the given point (-1, 0)?
Is 0 = -3(-1) - 3 true? Yes, it is true.